2024
DOI: 10.3390/f15020354
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Essential Role of Green Spaces during the COVID-19 Pandemic and Beyond

Mariusz Ciesielski,
Piotr Gołos,
Fruzsina Stefan
et al.

Abstract: The COVID-19 pandemic highlighted the essential role of urban and rural green spaces for societies coping with global public health crisis. During this particular time, a significant body of research was devoted to human–nature relationships, as well as the use and importance of green spaces, both from the management and visitors’ perspectives, along with the vital role of nature in human health and wellbeing. Furthermore, the pandemic experience induced new paradigms in spatial and urban planning, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%